A Mini Review : Clinically Significant Potential Drug-Drug Interactions In COVID-19 and Comorbid Therapy - Faizah, Ana Khusnul; Nurrahman, Nani Wijayanti Dyah; Putra, Oki Nugraha (UI Scholars Hub, 2020)
Coronavirus disease 2019 (COVID-19) is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and can be aggravated by comorbid diseases. In administering COVID-19 therapy, we need to consider potential drug-drug interactions (pDDIs) with comorbid drugs. Most patients with comorbid diseases get polypharmacy, therefore the risk of pDDIs increases. Potential drug-drug interactions can cause unwanted effects such as toxicity to death. There is no on-label therapy for COVID-19 but FDA has Emergency Use Authorization (EUA) for hydroxychloroquine, chloroquine, azithromycin, remdesivir, ritonavir, and lopinavir. Some COVID-19 treatment potential drug-drug interactions have a level of severity C and D, so there is a high need for close monitoring during drug administration or modification therapy.